BALLISTIC STRETCHING EXERCISES AND THEIR EFFECT ON EXPLOSIVE STRENGTH, FLEXIBILITY, STROKE LENGTH, AND STROKE FREQUENCY OF THE WORKING LIMBS IN YOUTH SWIMMERS OF WASIT GOVERNORATE CLUBS - Mutaman Jabar Mohamed Hussein; Hasan Hadi Abed Hasuwni Alhamrawi; Hayder Mahdi Dakhil Al hlew (Journal Olahraga Rekat (Rekreasi Masyarakat), 2026)
Background. The researcher focused on employing ballistic stretching exercises to develop certain forms of muscular strength and flexibility, which are considered essential requirements for swimmers. These exercises are distinguished by their ability to enhance flexibility through rapid, explosive movements performed within a specific range of motion, with the potential for progressive improvement through continued training, depending on the anatomical characteristics of the joint and muscle. Objectives. The study aimed to design ballistic stretching exercises and identify their effects on selected forms of strength and flexibility. Method. The researcher adopted an experimental method using a single-group design with pre- and post-tests. The research sample was intentionally selected and consisted of youth swimmers from Al-Kut Club in Wasit Governorate, aged (16–17) years, with a total of (10) participants. Statistical analysis was conducted using the Statistical Package for the Social Sciences (SPSS) to obtain the study results. Results. Significant at the level (0.05) when the error level ≤ or = (0.05), and the tabulated t-value = (2.262). The findings indicated that ballistic stretching exercises led to noticeable improvements in explosive strength of both the arms and legs, speed-strength, as well as flexibility. Conclusion. The development in swimming performance is attributed to the scientifically structured curriculum, which utilized appropriate intensity, volume, and density. The use of specialized equipment, such as resistance bands and weights during stretching, addressed performance deficits and increased training unit efficiency.